Consumer Protection Challenges in In-House Installment Agreements within The Real Estate Sector - Arya Sandi Yudha Libert; Yenny Eta Widyanti; Herlindah Herlindah (IBLAM LAW REVIEW, 2026)
house installment schemes within Indonesia’s real estate sector. In-house financing, managed directly by developers without financial institution supervision, creates structural risks due to unequal bargaining power, weak regulatory oversight, and the absence of safeguards for consumer funds. The research aims to examine legal gaps in the current housing and consumer protection framework and to formulate a preventive regulatory model. Using normative legal research with a comparative approach, this study evaluates Indonesian regulations and compares them with India’s Real Estate Regulation and Development Act 2016. The findings indicate that the absence of mandatory fund segregation exposes consumers to significant risks of project failure and fund diversion. The study concludes that Indonesia should adopt a mandatory escrow account mechanism, similar to India’s model, requiring a substantial portion of consumer funds to be deposited in a supervised account and released based on verified construction progress. Such reform would strengthen accountability, transparency, and consumer protection.